Stakeholder perspectives on depression management: A design thinking exploration for person-centered digital health - Sònia Moretó; Aïna Fuster-Casanovas; Andrea Duarte; Noemí Robles; Daniela Cabutto; Antoni Pérez-Navarro; Irene Lapuente; Emma Planas; Maria Padilla; Carme Carrion (PLoS ONE, 2026)
Introduction eHealth has the potential for managing depression and enhancing quality of life. Identifying end user needs and employing participatory methodologies that actively engage all stakeholders can improve user experience, usability and effectiveness. Materials and Methods Six face-to-face empathy workshops were conducted in three Spanish autonomous communities (Catalonia, Andalusia and Canary Islands) using design thinking methodologies, involving individuals with depression and mental health professionals. Data were analyzed using an iterative and inductive analysis approach. Objective To explore the perspectives of people diagnosed with depression and healthcare professionals involved in its management, using a design thinking methodology. Results Thirteen individuals with depression (10 women, average age 49.15, SD: 18.10) and 17 mental health professionals (11 women, average age 40.21, SD: 12.15) participated in empathy workshops. Three key themes emerged: the daily experience of depression, the potential of technology in managing depression, and emerging challenges to address. Discussion The intensity and daily experience of depressive episodes were influenced by various factors. Technologies, when used as a complement to face-to-face care, showed potential for managing depression. However, there were associated risks and challenges that need to be addressed. Conclusion It is essential to identify and understand the needs of end users and incorporate the perspectives of all stakeholders in the design and development of digital health interventions.